SELECTED CORRESPONDENCE OF VOLODYMYR POLIEK - Baran, Evgen (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Volodymyr Teodorovych Poliek (September 27, 1924-July 19, 1999) is one of the last classical bibliographers who was born, lived and died in Stanislaviv (Ivano-Frankivsk). The biobibliography of Volodymyr Poliek is extremely wide and has not yet been studied. His great work, which he did until the last days of his life - "Bio-bibliographic dictionary of the Precarpathian region" - remained unfinished and exists only in a newspaper version. Volodymyr Poliek’s epistolary is also extensive and almost unexplored. The scientist himself started publishing his correspondence in 1991, preparing several letters of Olha Duchyminska. In 2004 and 2013, selected correspondence of Volodymyr Poliek was printed by the author of these lines. In 2008, the part of the correspondence with Stanislav Vincenz was published by Olha Tsivkach. The purpose of the article: to acquaint readers with selected official correspondence of Volodymyr Poliek such as letters-answers from various periodicals and several copies of official letters of the researcher himself, which are stored in the room of Volodymyr Poliek in Vasyl Stefanyk Precarpathian National University. Research methods: precise-historical, comparative, descriptive. Scientific novelty: letters from Poliek’s archive published for the first time. The practical significance of the article is that its results can be used to study Poliek’s biography and understand the era in which the researcher used to live and work.